Plastic Vanitas and Amani Vanitas: Contextual Workshop, Residency, and Publication. - Neudecker, Mariele (BathSPAdata, 2021)
Emerging from residencies at the Museum of Design in Plastics and Amani, an abandoned post colonial science research centre in Tanzania, the Vanitas works question what constitutes an archive and how responses to it might forge new connections, shedding light on our anthropological heritage, sustainability and our relationship to the environment. This item contains documentation of an exploratory workshop in Finse Norway in 2013 on the Anthropology of Tropical and Arctic Field Stations, co convened by Wenzel Geissler, which was the starting point for Neudecker's Vanitas works. It also documents the artist's 2014 residency in Amani, an abandoned research station in Tanzania, including a pdf of her Amani photoworks. Neudecker's brief essay Echo, written about her experience in Amani can also be viewed in this item. It was included in the publication Traces of The Future: An Archeology of Medical Science In Africa which was edited by Professor Paul Wenzel Geissler, Guillaume Lachenal, John Manton and Noemi Tousignant. It was published by the University of Chicago Press in 2017. Photography courtesy of the artist and used with permission. The work is under copyright and may not be used without permission. Use of this repository acknowledges cooperation with its policies and relevant copyright law.